The Influence of Work-Life Balance and Work Environment on Gen Z Employee Loyalty in Indonesia - Rounia Hajjar .S; Fetty Poerwita Sary (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the influence of work life balance and the work environment on the loyalty of Generation Z employees in Indonesia. The research employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. The sampling technique used is purposive sampling, as the study focuses on individuals from Generation Z who are employed full-time in Indonesia. Data were collected through the distribution of questionnaires to 125 respondents who met the research criteria. The results show that work life balance has a significant influence on employee loyalty, the work environment also significantly influences employee loyalty, and both factors simultaneously have a significant effect on the loyalty of Generation Z employees in Indonesia. This study is expected to provide empirical evidence of a positive relationship between work life balance and the work environment in enhancing employee loyalty.